PERAN KEPOISIAN DAAM MENGATASI TINDAK PIDANA JUDI ONLINE DI PROVINSI BALI - M. Bayu Widya Bagaskara; setianto, muhamad jodi; hartono, made sugi (Universitas Pendidikan Ganesha, 2024)
This research aims to understand and explore the role of the police in combating online gambling crimes in Bali Province. In this study, the researcher uses an empirical legal research method with a descriptive approach. The data collection techniques include document studies, observations, and interviews. The sampling technique used is nonprobability sampling, specifically purposive sampling for determining subjects. The legal material analysis technique is qualitative. The results of the study indicate that the police in Bali Province, particularly the Bali Regional Police (Polda Bali), have undertaken various efforts to combat online gambling crimes. These efforts include cyber patrols, monitoring online gambling activities, tracking suspicious financial transactions, and direct actions against offenders. The police actions are conducted in accordance with applicable legal procedures and norms. However, in practice, cybercrime police face significant challenges. Major obstacles identified include the anonymity of online gambling users, the use of advanced technologies such as VPNs and IP Proxies by offenders, and the location of servers overseas, which complicates tracking and shutting down online gambling sites. Additionally, the lack of human resources trained in cybersecurity and digital forensics, as well as inadequate technological facilities, pose further challenges in handling online gambling cases. Administrative hurdles and coordination issues among government agencies, such as with the Ministry of Communication and Informatics (Kominfo), also slow down the law enforcement process.